Synthesis, Characterization and Luminescence Investigation of Sm3+ Doped Na3Bi(PO4)2 Phosphors for White Light Emitting Diodes (Journal of Scientific Research, 2026)
The synthesis of the Na3Bi(PO4)2: phosphor that has been activated by Sm3+ was accomplished by utilizing a wet-chemical reaction method. Transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), UV-Vis diffuse reflectance spectroscopy (DRS), and photoluminescence (PL) were all used to investigate the created Na3Bi(PO4)2:Sm3+ phosphors. By utilizing the reflectance spectra of undoped Na3Bi(PO4)2 and doped phosphors Na3Bi(PO4)2:Sm3+, researchers have determined the presence of strong energy absorption bands that appear in the region of 200–300 nm. Upon the stimulation of photoluminescence at 404 nm, the doped Na3Bi(PO4)2:Sm3+ phosphor exhibits a broad emission in the range of 400-600 nm, with a peak emission wavelength of 598 nm. In contrast, the phosphor Na3Bi(PO4)2 that had been doped with Sm3+ had three exceptionally strong emission bands at around 564 nm, 598 nm, and 645 nm, respectively. The transitions that caused the emissions were as follows: 4G5/2→ 6H5/2 (green emission), 4G5/2→6H7/2 (orange emission), and 4G5/2→6H9/2 (red emission). It has been established that the CIE (Commission Internationale de l’Éclairage) coordinates for the sample are as follows: x = 0.2841 and y = 0.3459. According to these findings, there is the possibility that the Na3Bi(PO4)2:Sm3+ phosphors that were synthesized have the potential to be used as a good option for white light emitting diodes and display devices.